Implications of the existence of opposition political parties as checks and balances in the implementation of democracy - Fahruddiana, Yosphia (PT. Batari Edu Calya, 2023)
The opposition plays an important role in monitoring government policies and programs or in fulfilling checks and balances. However, the opposition parties in parliament have always been in the minority along the long road of Indonesian populist democracy. This situation weakens the control function and widens the gap to uphold the will of the people. There are opposition parties which have always been a minority group in parliament which is even worse if the decision-making cannot be resolved by a joint decision. If this happens, the minority opposition forces cannot influence government policies. Consequently, when the votes of the parties in a coalition supporting the government have dominance in determining public policies, this will result in policies that are usually authoritarian in nature.